1996
DOI: 10.1097/00000542-199612000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Involvement in Hypoxic Dilation of Pial Arteries in the Cat

Abstract: Arteries and arterioles smaller than 200 microns are dilated by hypoxia, and nitric oxide contributes to this process. Nitric oxide synthesis may also be related to the regulation of resting vascular tone in arteries larger than 100 microns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The mechanism underlying this hypoxia-induced vasodilatation in selective vascular beds is not fully understood. In animal experiments, it has been demonstrated that nitric oxide synthase inhibitors attenuate hypoxia-induced cerebral vasodilatation (1,2,14,16). The present data are the first to show in humans that hypoxia-induced cerebral vasodilatation is mediated by nitric oxide, corroborating studies in the human forearm (4).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The mechanism underlying this hypoxia-induced vasodilatation in selective vascular beds is not fully understood. In animal experiments, it has been demonstrated that nitric oxide synthase inhibitors attenuate hypoxia-induced cerebral vasodilatation (1,2,14,16). The present data are the first to show in humans that hypoxia-induced cerebral vasodilatation is mediated by nitric oxide, corroborating studies in the human forearm (4).…”
Section: Discussionsupporting
confidence: 84%
“…The mechanism underlying this coupling between O 2 supply and cerebral vascular tone remains to be elucidated, although experimental data suggest that nitric oxide is involved (15). In various species it has been shown that nitric oxide synthase inhibitors attenuate hypoxia-induced cerebral vasodilatation (1,2,16). Recently, it has been shown that, in the human forearm, hypoxia-induced vasodilatation is mediated via the release of nitric oxide (4).…”
mentioning
confidence: 99%
“…Hypoxia dilates pial arterioles and/or increases cerebral blood flow in anesthetized rats (Buchanan and Phillis, 1993), dogs (McPherson et al, 1994), pigs (Pourcyrous et al, 1990;Wilderman and Armstead, 1997), lamb (van Bel et al, 1995), cats (Ishimura et al, 1996), and rabbits (Todd et al, 1997), as well as in conscious dogs (Audibert et al, 1995) and humans (Van Mil et al, 2002). Involvement of NO has been suggested in the response (Audibert et al, 1995;van Bel et al, 1995;Ishimura et al, 1996;Todd et al, 1997;Wilderman and Armstead, 1997;Van Mil et al, 2002).…”
Section: Pharmacology Of Neurogenic No In Blood Vesselmentioning
confidence: 99%
“…Involvement of NO has been suggested in the response (Audibert et al, 1995;van Bel et al, 1995;Ishimura et al, 1996;Todd et al, 1997;Wilderman and Armstead, 1997;Van Mil et al, 2002). Prostanoids (Pourcyrous et al, 1990;Leffler and Parfenova, 1997), methionine enkephalin released by NO and/or cyclic GMP (Armstead, 1995a), adenosine (Armstead, 1997a), and cytochrome P450 epoxygenase metabolites (Fredricks et al, 1994) are also involved in the response in rats and pigs.…”
Section: Pharmacology Of Neurogenic No In Blood Vesselmentioning
confidence: 99%
“…For example, in the vasculature, hypoxia is known to stimulate EDHF release and NO contributes to hypoxic vasodilation in forearm resistance vessels in humans (Pohl & Busse, 1989; Blitzer et al ., 1996). In cat cerebral arterioles less than 100 μm in diameter, inhibition of NO synthase (NOS) attenuated hypoxic vasodilatation without having a direct vasoconstrictor effect (Ishimura et al ., 1996). In vivo experiments on the rat show NOS inhibition attenuates hypoxic cerebral vasodilatation (Reid et al ., 1995).…”
Section: Introductionmentioning
confidence: 99%